2006
DOI: 10.1097/01.brs.0000197410.92525.10
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Osteopenia in Adolescent Idiopathic Scoliosis–Association With Abnormal Pubertal Growth, Bone Turnover, and Calcium Intake?

Abstract: Results from the current study showed that an abnormally faster growth rate and higher bone turnover in the patient with AIS might lead to increased bone dimensions. Calcium intake in patients with AIS was very low and likely to be insufficient for normal bone mineralization. Therefore, low bone mass in AIS may result from abnormal bone mineralization qualitatively and quantitatively and, thus, fails to catch up with increased bone growth during the peripubertal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 41 publications
(32 reference statements)
5
78
0
1
Order By: Relevance
“…Volumetric BMD (vBMD) of the distal tibia was evaluated by peripheral QCT (Densiscan 2000, Scanco Medical, Basselsdorf, Switzerland). Precision errors of using DXA in measuring BMC and BMD at the lumbar spine and proximal femur were 1.1%-3.7% while the CV in measuring vBMD of the distal tibia was less than 0.8-0.99 by using pQCT in our Centre [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volumetric BMD (vBMD) of the distal tibia was evaluated by peripheral QCT (Densiscan 2000, Scanco Medical, Basselsdorf, Switzerland). Precision errors of using DXA in measuring BMC and BMD at the lumbar spine and proximal femur were 1.1%-3.7% while the CV in measuring vBMD of the distal tibia was less than 0.8-0.99 by using pQCT in our Centre [8].…”
Section: Methodsmentioning
confidence: 99%
“…Anthropometric parameters including weight, height, corrected height (adjusted for trunk loss), leg length and arm-span were measured by standard methods [7,8]. The age onset of menarche was also obtained.…”
Section: Methodsmentioning
confidence: 99%
“…One study indicated that decreased differentiation ability of mesenchymal stem cells may contribute to osteopenia in individuals with AIS 38 . Environmental factors such as diet, calcium intake, vitamin-D level, and exercise have been related to AIS 39,40 . A greater threshold for disease expression in males may also explain why AIS appears to skip generations in some families, particularly when passed through unaffected males.…”
Section: Discussionmentioning
confidence: 99%
“…Lee [11] reported that patients with AIS had low calcium intake and this was a contributing factor in the development of scoliosis. Cheung et al [4] suggested that the low bone mass could be due to abnormally faster growth at adolescence with low calcium intake cause abnormal mineralization. Apart from the above mentioned factors low BMI could be a contributing factor in low BMD in scoliotic patients.…”
Section: Discussionmentioning
confidence: 99%